Investigating ELFA: University Students' and Lecturers' Perceptions, Challenges, and Strategies in English Medium Programs - Abbas Hadizadeh; Gaelle Youbi (Journal of Research in Social Sciences and Language)
The present study investigates the perceptions and practices of a group of university students and instructors at an English Medium university in Northern Cyprus. The study examines the relationship between attitudes and perceptions towards English Medium Instruction (EMI) and English as an Academic lingua franca (ELFA). The research adopts a mixed-methods approach, incorporating a survey distributed among 200 students and interviews conducted with 4 students and 6 instructors. The survey results are analyzed with SPSS 23 to provide descriptive statistical analysis, correlation, and regression analysis. The interview data undergoes thematic analysis to uncover patterns and provide qualitative insights. The study indicates differing perceptions and attitudes between students and instructors. Instructors tend to perceive students’ attitudes towards EMI/ELFA as negative, while students themselves exhibit positive attitudes toward these instructional methods. Additionally, the study sheds light on the significant challenges faced by both students and instructors, including issues related to low language proficiency, self-confidence, and comprehension problems within the EMI context. The research also highlights the diverse strategies employed by students to overcome these challenges. The findings have potential implications for other similar EMI contexts.